SwiftCare: specialist appointment system - Yasir, Nurul Shafika Natasha (2025)
SwiftCare refers to an intelligent outpatient appointment managing system, which will elevate the efficiency and effectiveness of scheduling of appointments of healthcare facilities in Malaysia. This system incorporates the use that mention real-time appointment scheduling, the capability to customize self-service on individual events, emergency appointment preferences, and compatibility with electronic medical records and scheduling appointments to coordinate patient influx in an effective manner. Made with an agile approach, the SwiftCare application has been developed on trusted platforms like Android Studio and Firebase that make it secure, scalable, and easy to navigate. The app is accessibility-friendly and will have such features as large fonts, user-friendly interface, and intelligent algorithms that will help a user to build schedules, regardless of the background or limited digital literacy. In real time, the system can make on the fly adjustments to appointment schedules and minimize clashes and maximize resources use where emergency cases are involved without interfering with normal processes. SwiftCare focuses on major problems in the healthcare sector, such as long queues in front of hospitals, overlapping schedules and in General administration effectiveness, but the goal is to enhance patient satisfaction. This solution meets the current needs of users through the implementation of innovative technologies which can provide a modern, responsive, and patient-centered approach to appointments. SwiftCare supports an increase in the need for digital change in the healthcare industry to provide more effective and inclusive care services.